The role of public incentives in promoting innovation: An analysis of recurrently supported companies - Cátia Rosário; Celeste Amorim Varum; Anabela Botelho (Economies, 2024)
This study delves into the intricate relationship between corporate innovation and public support, underscoring innovation's vital role in driving economic growth and competitiveness. Recognizing the multifaceted nature of innovation, from product and process improvements to organizational and marketing innovations, we examine how specific business characteristics and sectoral specificities condition access to public research and development (R&D) support, both nationally and at the European level. We analyze data from five Community Innovation Survey (CIS) reports spanning from 2008 to 2018 using ordered logit models. This approach evaluates the likelihood of companies receiving recurring public support for R&D based on internal R&D investments, interinstitutional collaboration, employee qualifications, and sectoral attributes. The findings reveal that internal R&D investments and collaboration with other entities significantly increase the likelihood of a company receiving recurrent public support. Furthermore, companies in high-tech sectors are more prone to receive public assistance. However, the analysis of European support shows no widespread statistical significance of the considered variables, suggesting the influence of evolving funding policies and an imbalanced dependent variable distribution. We conclude that the ability to secure public R&D support is influenced by a mix of company-internal and -external factors, highlighting the need for comprehensive and adaptable innovation policies. This study's limitations, including potential sample non-representativeness and the dynamics of funding policies, underscore the importance of further, more encompassing research.
Keywords: 330; CIS; cooperation; innovation; logit model; public support; sector of business activity